2016
DOI: 10.1186/s12913-016-1557-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic crisis, austerity and unmet healthcare needs: the case of Greece

Abstract: BackgroundThe programme for fiscal consolidation in Greece has led to income decrease and several changes in health policy. In this context, this study aims to assess how economic crisis affected unmet healthcare needs in Greece.MethodsTime series analysis was performed for the years 2004 through 2011 using the EU-SILC database. The dependent variable was the percentage of people who had medical needs but did not use healthcare services. Median income, unemployment and time period were used as independent vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 35 publications
8
86
2
2
Order By: Relevance
“…The Greek healthcare system suffered major spending cuts, but the underlying inefficiencies were not effectively addressed226, forcing large numbers of health professionals out of the country27. Moreover, the introduction of user fees and co-payments shifted some of the cost to patients adding further barriers to timely healthcare access213. Our survey data showed that average OOPE almost doubled between 2010 and 2015, mostly due to greater number of people being required to pay for prescription drugs28 and healthcare services, either as user fees for public services or increasing use of private services to avoid deteriorating conditions in the public healthcare system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Greek healthcare system suffered major spending cuts, but the underlying inefficiencies were not effectively addressed226, forcing large numbers of health professionals out of the country27. Moreover, the introduction of user fees and co-payments shifted some of the cost to patients adding further barriers to timely healthcare access213. Our survey data showed that average OOPE almost doubled between 2010 and 2015, mostly due to greater number of people being required to pay for prescription drugs28 and healthcare services, either as user fees for public services or increasing use of private services to avoid deteriorating conditions in the public healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that the crisis has resulted in increases in poor self-rated health6, depression7, suicide attempts8, homicides9, infant10 and all-cause mortality11, outbreaks of infectious diseases12, restrictions in access to healthcare213, and mortality due to adverse events during medical treatment14. However, most of these studies included data only from the first two years of the crisis and only report short-term effects.…”
mentioning
confidence: 99%
“…Thus, in the vulnerable post-diagnosis phase, aftercare and follow-up aim to stabilise treatment effects and prevent relapse or re-admission. Barriers to healthcare access have emerged as one of the main negative consequences of austerity, as the proportion of Greek adults who reported unmet healthcare needs more than doubled in just 5 years, with 12.2% of respondents citing cost as the main reason for not receiving treatment or diagnostic tests [14,15,95]. Furthermore, from 2009 onwards, public pharmaceutical expenditure followed a downward trend, from approximately €5.3 billion in 2009 to approximately €2 billion in 2014, notably by cutting the prices paid for drugs and promoting the increased use of generics [14,[93][94][95].…”
Section: Tertiary Prevention Of Copd In the Years Of Economic Crisismentioning
confidence: 99%
“…Economic downturns have historically been associated with increases in all-cause mortality [5][6][7][8]. In the Greek population, early reports have suggested a negative effect of financial crisis on public health [3, [9][10][11][12], and remarkably on respiratory health [1, 9,10,[13][14][15]. The impact of the Greek downturn on respiratory health was apparent even though most studies used data covering only the first years of the crisis and reported its short-term effects [16].…”
Section: Introductionmentioning
confidence: 99%
“…During 2008–2015, the gross domestic product decreased by more than a quarter, unemployment rapidly increased from 7.8% to 24.9% and a series of austerity measures (eg, tax increases, salary cuts) were introduced in the context of a large-scale fiscal consolidation programme 15. Evidence suggests that living conditions and health trends deteriorated,16 17 while patients face unmet needs and increased barriers to accessing healthcare 18. These adverse developments had an impact on well-being and life satisfaction in Greece 19…”
Section: Introductionmentioning
confidence: 99%